Performance Testing of Cross Wind Turbine Model with Capacity of 10 W - Achdi, Endang; Sonawan, Hery; Setiadi, Yudi (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2024)
Wind is a significant potential renewable energy source for electricity generation. Currently, there are two commonly used types of wind turbines: horizontal-axis and vertical-axis wind turbines. Both types are designed to harness the energy from horizontally moving wind. However, in reality, wind often moves erratically, especially in urban areas with tall buildings. To address this, a cross-axis wind turbine model has been developed to capture energy from randomly moving wind. This turbine model has 10 horizontal blades and 5 vertical blades. Previously, performance testing of this wind turbine model used a 60 W capacity dynamometer generator, but the wind turbine's output power didn't reach the required high torque and rotational speed. In this research, a 40 W capacity generator was used to resolve the previous issues. The parameters measured in this testing include wind speed, turbine rotational speed, voltage, and current. The testing was conducted at wind speeds of 5.3 m/s, 5.8 m/s, 6.3 m/s, and 6.8 m/s, with variations in the blade pitch angles set at 20°, 25°, and 30°. The results of the testing and analysis showed that the maximum performance coefficient of this wind turbine was 7.54%, achieved at a wind speed of 6.3 m/s with a blade pitch angle of 25° and a tip speed ratio of 1,08. The higher the wind speed, the shorter the time required to reach a constant rotational speed. At a wind speed of 6.3 m/s with a blade pitch angle of 25°, it took 30 seconds to reach a constant rotational speed.